2006
DOI: 10.1002/aoc.1065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublethal levels of tributyltin chloride on a new toxicity test organism, Liza saliens (osteichthyes, mugilidae): a histological study

Abstract: The histopathological effects of 10 −7 and 10 −9 M tributyltin(IV)chloride,TBTCl, solutions on different Liza saliens organs have been studied by light microscope. The fish were sacrificed after 3-4 h incubation in 10 −7 M TBTCl solution or after 15 days incubation in 10 −9 M solution. The observed histopathological changes were dose-and time-dependent. The 10 −7 M TBTCl concentration resulted in major damage to the gill epithelium, indicating that TBTCl primarily interfered with the respiration, osmoregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
4
0
2
Order By: Relevance
“…In this context, fishes represent a crucial role as energy carriers from the lowest to higher trophic levels ( Van der Oost et al 2003). Fishes are able to bioaccumulate BTs at two or three levels of magnitudes (D'Agati et al 2006), even when exposed to low environmental concentrations (ng mL −1 or ng g −1 ) (Meador et al 2002). TBT toxicity is well described in the literature, mainly with regard to the effects on the endocrine system, where cytochrome P450 is inhibited and causes masculinization in gastropod females (Fernandez et al 2005;Leung et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, fishes represent a crucial role as energy carriers from the lowest to higher trophic levels ( Van der Oost et al 2003). Fishes are able to bioaccumulate BTs at two or three levels of magnitudes (D'Agati et al 2006), even when exposed to low environmental concentrations (ng mL −1 or ng g −1 ) (Meador et al 2002). TBT toxicity is well described in the literature, mainly with regard to the effects on the endocrine system, where cytochrome P450 is inhibited and causes masculinization in gastropod females (Fernandez et al 2005;Leung et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The hystopatological study also demonstrated that the DBT-derivatives exhibit a specific toxicity on some target organs: 6 and 8 heavily modify the pancreatic structure by destroying the erythrocytes with a consequent hemoglobin pouring (observed as a fine granular pink pigment outside the organ). Such induced alterations, however, appear less severe than those observed for TBTCl on the same species; [22] alterations in eyes, gills, muscles, liver, intestine, pancreas and heart were already observed at 10 −7 M TBTCl, along with thymus atrophy, spleen reduction and alteration of head and kidney. Muscle fibres appeared normal after treatment: the treated fishes moved as the controls, and the histological study showed that only for 6 and 8 the muscle fibres were slightly detached.…”
Section: Biological Investigationmentioning
confidence: 65%
“…Histology has provided a rapid method to detect effects of the pollutants in various fish tissues and organs. [18 -21] In this respect these diorganotin(IV) derivatives have been tested on Liza saliens juveniles, a species already usefully employed to evaluate chemical toxicity, [22] and their biological activity has been compared with the effects of tributyltin(IV) chloride [22] using light microscope and histopathological techniques. In fact, in aquatic systems, tributyltin(IV) chloride is considered to be the most toxic organotin moiety, 10-100 times more toxic than dibutyltin(IV) moiety and its toxicity decrease with progressive de-alkylation to di-and mono-organotins.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies 7–11 have shown that low doses of some diorganotin(IV) compounds show antitumor activity via a gene‐mediated pathway in the cancer cells, leading to new research on antitumor organotin(IV) compounds. It is well known that organotin(IV) compounds are important in cancer chemotherapy owing to their apoptosis‐inducing property 12, 13.…”
Section: Introductionmentioning
confidence: 99%